Quality of services and prices in promoting customer satisfaction and customer loyalty services of container transportation facilities. Case Study at PT. Yang Ming Shipping Indonesia - Kusumo, Dhanang Suryo; Rachbini, Didik J.; Rekarti, Endi (Technium Social Sciences Journal, 2021)
The study is aimed to determine the effect of the quality of service , price to encourage the satisfaction of customers and loyalty of customers the services of a means of conveyance crate packing . Customers from PT. Yang Ming Shipping Indonesia was taken as the respondent , both primary and secondary data were used in the study . Secondary data is taken from various sources such as journals , books and other data . Primary data was collected using a questionnaire which was distributed to the target respondents . Using the technique of accidental sampling, a total of respondents who collected a number of 140 respondents . Path analysis is applied in this study . The results show that service quality has a significant effect on customer satisfaction . Price has a positive and significant effect on customer satisfaction . and d itemukan that the quality of services has the effect of significantly towards consumers loyal. Price memilikipenagruh positive and significant to consumers loyal, things were equally found their influence posiif and exhibited significantly that occur between the satisfaction of customers to consumers loyal. At the level of managerial , research is giving a donation to the PT. Yang Ming Shipping Indonesia, to improve service quality and price if you want customer satisfaction and customer loyalty to increase .